ANALISIS KELAYAKAN USAHATANI JAHE GAJAH DI KECAMATAN DONGKO KABUPATEN TRENGGALEK - Sugeng Bayu E; Navita Maharani; Erlin Widya F (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
Ginger is a leading Indonesian biopharmaceutical commodity. East Java is one of the centers of biopharmaceutical plant production in Indonesia. As an export commodity, demand for ginger continues to increase along with the development of the herbal food and beverage industry. However, data on ginger production and harvested area in Trenggalek Regency from 2019 to 2023 show fluctuating production results. The high and low production results of a commodity are influenced by many factors. One of them is poor allocation of production inputs, resulting in less than optimal output. This study aims to identify the production factors used and to determine the feasibility of elephant ginger farming in Dongko District, Trenggalek Regency. This study was conducted from December 2023 to January 2024. The method and data analysis used were descriptive quantitative analysis. Data analysis used income analysis (π = TR–TC) and farming feasibility. The results show that elephant ginger farming is profitable and feasible to run. Despite the limited technology (agricultural tools/machines) used, respondent farmers are able to produce high output by selecting good seeds. Elephant ginger seeds must meet the criteria, namely having at least 2-3 brightly colored shoots and a smooth texture.